2009
DOI: 10.1002/bio.1140
|View full text |Cite
|
Sign up to set email alerts
|

New luminol chemiluminescence reaction using diperiodatoargentate as oxidate for the determination of amikacin sulfate

Abstract: A new chemiluminescence (CL) reaction between luminol and diperiodatoargentate [K(2) [Ag (H(2)IO(6)) (OH)(2)]] was observed in alkaline medium. The CL intensity could be greatly enhanced by amikacin sulfate. Therefore a new CL method for the determination of amikacin sulfate was built by combining with flow injection technology. A possible mechanism of the CL reaction was proposed via the investigation of the CL kinetic characteristics, the CL spectrum and the UV absorption spectra of some related substance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…It was confirmed that in the CL reaction of luminol and DPA, the exited state of 3‐aminophthalate was an emitter . So, according to previous studies of the oxidation of amikacin sulphate, dopamine and paracetamol , the possible mechanism of the luminol–DPA–cysteine system in the absence of β ‐CD–Fe 3 O 4 MNPs inclusion complexes was proposed, and is shown in Scheme . In the prior equilibrium step 1, (OH – ] deprotonates the DPA to give a deprotonated diperiodatoargentate(III); in the second step, displacement of the ligand, periodate, takes place to give free periodate.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…It was confirmed that in the CL reaction of luminol and DPA, the exited state of 3‐aminophthalate was an emitter . So, according to previous studies of the oxidation of amikacin sulphate, dopamine and paracetamol , the possible mechanism of the luminol–DPA–cysteine system in the absence of β ‐CD–Fe 3 O 4 MNPs inclusion complexes was proposed, and is shown in Scheme . In the prior equilibrium step 1, (OH – ] deprotonates the DPA to give a deprotonated diperiodatoargentate(III); in the second step, displacement of the ligand, periodate, takes place to give free periodate.…”
Section: Resultsmentioning
confidence: 66%
“…DPA complex was prepared according to the literature , with some modifications, such as using a micro‐filter to separate the precipitate, and shielding the solution container from light with aluminium foil during the heating process. Spectroscopic methods were used to confirm the synthesized complex.…”
Section: Methodsmentioning
confidence: 99%
“…However, a relatively high LOD for amikacin was obtained by using the same CL system in a conventional FI method [22]. Conventional FI methods using other luminol systems have been also described for several individual AG antibiotics [26][27][28], but the method described here is the first one which uses a microfluidic system for AG determination using CL detection.…”
Section: Optimization Of Variablesmentioning
confidence: 95%
“…A comparison of the figures of merit of this work with those of other methods for the determination of aminoglycoside antibiotics involving CL detection [22,[24][25][26][27][28][29][30] is shown in Table 3. As can be seen, the luminol-hydrogen peroxideCu(II) system has been described for the CL detection of amikacin alone [24] and AG mixtures [25] by liquid chromatography, reaching very low LOD values in this last method, which includes a previous preconcentration step.…”
Section: Optimization Of Variablesmentioning
confidence: 98%
“…A lot of researchers had employed various assay methods for determining some aminoglycosides including gentamicin in different delivery systems. These include: microbiological [5], polarographic [6], chemiluminescence [7], capillary electrophoresis [8], immunoassay [9], thin layer chromatographic [10], high performance liquid chromatographic [11], spectrofluorimetric [12], and spectrophotometric [13,14] methods.…”
Section: Introductionmentioning
confidence: 99%